Varietal evaluation of promising maize genotypes in mid hills of Nepal - Neupane, Bipin; Poudel, Ankur; Wagle, Pradeep (Journal of Agriculture and Natural Resources, 2020)
The varietal evaluation of hybrid maize (Zea mays L.) genotypes with desired performance is one of the main objectives of maize breeding program. Fourteen hybrid maize genotypes were evaluated for 17 quantitative and nine qualitative traits in randomized complete block design with three replications at Sundarbazar, Lamjung, Nepal during May to September, 2019. The major objective was to identify superior genotypes based on genotypic and phenotypic variability, heritability, genetic advance, and correlation between grain yield and yield associated traits. We observed significant differences for 17 quantitative traits among the tested genotypes. Large variation was observed for grain yield among genotypes. Genotype RL-24-0/ RL-111 had the lowest yield (5.53 mt/ha) and Pioneer had the highest yield (11.98 mt/ha) whereas check variety Rampur Hybrid-10 yielded of 8.23 mt/ha. Grain yield showed highly significant positive correlations with stem girth (r= 0.67) and number of ears (r=0.6), but significant negative correlation with anthesis-silking interval (r= -0.55). The dendrogram grouped 14 genotypes into four clusters. Cluster I incorporated the highest number (five) of genotypes, which also had highest cluster mean (average yield of 10 mt/ha) for grain yield. Traits namely test weight, ear aspect, anthesis-silking interval, number of ears, and tassel branching had high genotypic and phenotypic coefficient of variations, and heritability along with high genetic advances, indicating that these traits can be considered for maize breeding program.